Monotheism and religious experience - Webb, Mark Owen (Cambridge elements Elements in religion and monotheism, 2024)
"In the monotheistic traditions, there are people who report having special experiences that justify their monotheistic beliefs. They see, hear, or otherwise experience directly the one true God, ruler of the universe. In order to understand what is going on in these experiences and how we should respond to reports of these experiences, it is important to understand what religious experiences can and can't be, what the claim of monotheism entails, and therefore how what reports of such experiences mean, both for the experiencer and for the recipient of the report"--